Pengembangan Buku Hitung Perkalian untuk Siswa Sekolah Dasar - Rohadi, Veny (Jurnal Pendidikan Indonesia, 2025)
This study aims to develop and assess the feasibility of the Multiplication Calculation Book for elementary school students. The method used is Research and Development (R&D) with six stages, namely potential and problem identification, product design, design validation, limited trials, field trials, and mass production. The validation results show that this book is very feasible to use, with an assessment from material experts of 90%, media experts of 88%, and user responses of 95%. The application of this book in mathematics learning can help students understand the concept of multiplication gradually, increase concentration, and develop speed and precision in counting